Enhanced opto-non-linear properties of low cost deposited pure and Ni@PbI2/glass nanostructured thin films for higher order non-linear applications. (October 2021) - Shkir, Mohd; Khan, Mohd Taukeer; Ali, H. Elhosiny; Yousef, El Sayed; Algarni, H.; AlFaify, S.
Abstract: Herein, thin films of PbI2 with different Ni-doping concentrations (0.0, 1.0, 3.0, 5.0 and 7.5 wt%) have been fabricated using spin coating method. The fabricated films possess a hexagonal crystalline structure and growth along the (001) plane, as-confirmed by XRD analysis. EDS elemental-mapping confirmed the uniform doping of Ni throughout the PbI2 films. SEM images reveal the formation of nanoparticles/sheets with sizes of ⁓100 nm in the fabricated films. An optical absorption study reveal the change in absorption edge of PbI2 observed upon Ni doping. The fabricated films are highly transparent (i.e. 80–86%) in the visible to near-infra red region. The energy gap of PbI2 was determined to be 2.34 eV, which increased to 2.45 eV for the 5 wt% Ni@PbI2 film. The fabricated films show photoluminescence quenching when doped with Ni. The refractive index values were determine to be between 1.73 to 3.37 in the whole region studied. Furthermore, the dielectric-electrical-non-linear optical parameters were also determined. The χ ( 1 ), χ ( 3 ) and n ( 1 ) values were estimated to be in range of 0.16–0.83, 1.1 × 10 −13 to 7.8 × 10 −11  esu and 2.3 × 10 −12 to 8.7 × 10 −10  esu, respectively. It was noticed that these parameters were enhanced upon Ni doping up to 5.0 wt%. The enhanced opto-non-linear properties of PbI2 by Ni doping makes it a suitable candidate for optoelectronic applications. Graphical abstract: Image 1 Highlights: A low-cost and facile fabrication of nanostructured Ni@PbI2/glass thin films has been achieved. XRD, FT-Raman and EDX/e-mapping confirmed the synthesis of PbI2 films with hexagonal 2H–PbI2 polytypes. The energy gap of pure and Ni doped-PbI2 was determined between 2.34–2.45 eV. The PL emission intensity was quenched upon Ni doping in PbI2. Non-linear parameters such as χ (3) and n (2) were enhanced to 7.8 × 10 −11  esu and 8.7 × 10 −10  esu upon Ni doping, respectively.